Post-mortem artifacts mimicking blunt force trauma: a systematic review for forensic differential diagnosis (International Journal of Occupational Safety and Health, 2026)
Introduction: The accurate differentiation between genuine blunt force trauma and various post-mortem artefacts is a critical challenge in forensic death investigation, directly impacting the determination of the manner of death. Post-mortem changes, ranging from decomposition processes to animal activity, often produce lesions that closely mimic antemortem injuries. The primary objective of this study is to systematically identify and evaluate the diagnostic criteria used to differentiate genuine blunt force trauma from post-mortem artefacts.Methods: A comprehensive search was conducted across five major databases (PubMed, Scopus, Web of Science, Embase, and Cochrane Library) covering literature from their inception until December 2025. Unlike previous narrative reviews, this study employs a systematic methodology adhering to PRISMA 2020 standards. Data collection involved independent screening and extraction by two reviewers, focusing on morphological, histological, and analytical differentiation criteria. Methodological quality was appraised using JBI tools, and evidence certainty was assessed using the GRADE approach.Results: The findings emphasize that the presence of a vital reaction, primarily manifested through hemorrhage and inflammation, remains the most essential diagnostic indicator. Specific indicators such as fracture edge characteristics, skeletal surface coloration, and anatomical distribution of lesions are also identified as key discriminators. Following the primary filter, the algorithm diverges into two main evaluation pathways: one focusing on verifying trauma characteristics (e.g., injury patterns consistent with BFT) and the other on validating artefact characteristics (e.g., consistency with taphonomic processes). Additionally, the framework incorporates a distinct, parallel evaluation for animal activity, necessitating a specific analysis of marks and patterns (e.g., gnawing or punctures) to distinguish scavenger damage from mechanical trauma.Conclusion: This review provides a standardized diagnostic hierarchy and a decision tree to minimize subjective assessment in medico-legal investigations. By integrating advanced imaging and microanalytical approaches with traditional morphological observation, forensic practitioners can improve diagnostic reliability and ensure the integrity of the judicial process.